Student atlas of the world. (Boston : Tuttle, 1993)
Contains an informative guide to contemporary geographical issues, 128 pages of maps including the new nations of the former U.S.S.R. and Central and Eastern Europe, and a compendium of world geographical data.
Library Journal.
School Library Journal.
Wilson's Junior High School.
7-9
Adult
Keywords: Atlases; Atlases